Why the Raven Calls the Canyon : Off the Grid in Big Bend Country - Klepper, E. Dan (Book collections on Project MUSE., 2017)
Fresno Ranch, an abandoned horse and mule operation located in a remote stretch of the Rio Grande River bordering Mexico, gives evidence of a human presence spanning centuries. The ranch saw a period of entrepreneurial mule breeding and ranching, and ownership by Texas artist and publishing heiress Jeanne Norsworthy, who built an off-the-grid, hand-constructed adobe studio on the premises. Photographer and freelance writer E. Dan Klepper spent seven years, off and on, living and working at Fresno Ranch. By 2008, when the 7,000-acre property was acquired by the Texas Parks and Wildlife Departme.